Comparative analysis of cultivated and wild olive genotypes to salinity and drought stress - Tadić, Josip; Dumičić, Gvozden; Veršić Bratinčević, Maja; Vitko, Sandra; Liber, Zlatko; Radić Brkanac, Sandra (Frontiers in Plant Science, 2024)
The Mediterranean region's harsh conditions, characterized by low rainfall, high solar radiation, and elevated temperatures, pose challenges for vegetation, particularly in the face of climate change. Cultivated olive (Olea europaea subsp. europaea var. europaea) holds historical and economic significance as one of the oldest crops in the Mediterranean. Due to their high germplasm diversity and greater flowering abundance compared to the offspring of cultivated olives, wild olives (Olea europaea subsp. europaea var. sylvestris) could be utilized for selecting new olive cultivars capable of adapting to a changing climate. This research aimed to compare the effects of salt and drought stress on wild and cultivated genotypes by analyzing morphological, physiological, and biochemical parameters. Results showed that shoot length, shoot dry mass, and leaf area are key drought stress indicators in wild olive trees. The results indicated the olive trees more susceptible to salinity stress had lower Na + and Cl -concentrations in their leaves and took longer to stabilize salt ion levels. Decreased K + content in roots across all treatments indicated a general stress response. The uptake of Ca 2+ appears to be the most energy-efficient response of olive trees to short-term salinity and drought. In contrast to proline and malondialdehyde, trends in superoxide dismutase activity suggest that it is a reliable indicator of salinity and drought stress. Regarding olive adaptability to salinity stress, promising results obtained with two wild olive genotypes merit their further physiological study.